Shore to landward transect burrow diversity of fiddler crab in a tropical intertidal coast of Chittagong in Bangladesh - Khan, Mst Mansura; Khan, Mohammad Sadequr Rahman (Research in Agriculture Livestock and Fisheries, 2017)
Burrows indicate the abundance and distribution of fiddler crab in an intertidal coast that varies with structure and morphology within intertidal habitats. We observed fiddler crab burrow density and characters (burrow length, depth, diameter and volume) within randomly selected six 1m2 quadrate from three intertidal habitats: higher saltmarsh, mangrove pool (a small ditch distributed within mangrove) and mangrove land through field surveys in a coast of Chittagong, Bangladesh. Burrows were observed and counted for density estimation, and burrow characteristics were studied through excavating 10 representative burrows from each quadrate of each habitat. Spearman correlation was used to relate between the distances (from shore towards land) and burrow characters. Transect starting from saltmarsh as base towards mangrove land showed burrow density decreased from shore to higher intertidal habitat. Simultaneously, higher burrow length and diameter were observed landward and contrariwise shoreward. Burrow prevalence in mangrove pools represents fiddler crabs are abundant within land and shore interface presumably due to the dual privilege of easy burrowing and moist condition required for gill ventilation. Res. Agric., Livest. Fish.4(2): 131-140, August 2017